2000
DOI: 10.1016/s0735-1097(00)00848-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal reconstruction of the arterial wall with endothelial cell/glue matrix reduces restenosis in an atherosclerotic rabbit

Abstract: The attachment of EC after angioplasty can be greatly improved with fibrin glue matrix. The near 70% endothelial coverage achieved by this method resulted in a significant reduction of restenosis in atherosclerotic rabbit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…To improve endothelial-cell attachment to vascular substitutes, commercial adhesive substances, such as fibrin glue, have been used. [31] These biological substances suffer from being hydrolyzed and thus do not exhibit the required properties for clinical applications. [32] In order to improve endothelial-cell adhesion properties, we coated the luminal surface of cryopreserved umbilical arteries by a thin PSS/PAH polyelectrolyte multilayer film.…”
Section: Resultsmentioning
confidence: 99%
“…To improve endothelial-cell attachment to vascular substitutes, commercial adhesive substances, such as fibrin glue, have been used. [31] These biological substances suffer from being hydrolyzed and thus do not exhibit the required properties for clinical applications. [32] In order to improve endothelial-cell adhesion properties, we coated the luminal surface of cryopreserved umbilical arteries by a thin PSS/PAH polyelectrolyte multilayer film.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have shown that autologous venous ECs seeding can repopulate the ECs denuded arterial wall and reduce neointimal proliferation [10,[22][23][24][25], mature autologous venous ECs are heterogenic compared to arterial ECs and surgical operation is also unavoidable to acquire ECs. Therefore, one of the major reasons for limited application of cell transplantation in injured vascular diseases lies in the poor source of appropriate cells.…”
Section: Discussionmentioning
confidence: 97%
“…ECs were enzymatically isolated from the rabbit aorta and cultured as previously described [10]. The cells of passage 3-5 were used for experiments.…”
Section: Rabbit Ecs Primary Culturementioning
confidence: 99%
“…The endothelium is critical for preserving vascular homeostasis, serving not only as a physical barrier but also as a source of biologically active compounds [1]. Research has shown that xenogeneic and allogeneic endothelial implants reduce intimal hyperplasia and thrombotic occlusion [1,5,7].…”
Section: Introductionmentioning
confidence: 99%